2019
DOI: 10.1016/j.supflu.2018.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supercritical CO2 and olive leaf extract on the structural, thermal and mechanical properties of an impregnated food packaging film

Abstract: Poly(ethylene terephthalate)/polypropylene (PET/PP) films containing olive leaf extract (OLE) were obtained by supercritical solvent impregnation (SSI) in batch (BM) and semi-continuous (SM) modes.The study focused on the impact of pressure, temperature, CO2 flow and OLE on the properties of the impregnated films. Thermal analysis of non-impregnated samples revealed a decrease in the crystallinity of PP layer treated at 35 ºC and an increase in the Tg of PET treated at 55 ºC due to CO2 sorption. In impregnated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 86 publications
3
19
0
Order By: Relevance
“…When the pressure raises, the density of the supercritical fluid increases, which may favour both the swelling of the matrix and the solubility of the compounds. This behaviour agrees with the literature on the impregnation of polyester and cotton natural fibers with natural extracts, as well as on the impregnation of PET/PP films with natural extracts [ 42 , 45 , 64 ]. Based on these results, a pressure of 50 MPa was selected for the experiments to be carried out later on.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…When the pressure raises, the density of the supercritical fluid increases, which may favour both the swelling of the matrix and the solubility of the compounds. This behaviour agrees with the literature on the impregnation of polyester and cotton natural fibers with natural extracts, as well as on the impregnation of PET/PP films with natural extracts [ 42 , 45 , 64 ]. Based on these results, a pressure of 50 MPa was selected for the experiments to be carried out later on.…”
Section: Resultssupporting
confidence: 91%
“…It was observed that an increase of the C 2 H 5 OH:H 2 O percentage had in general a negative effect on the impregnation loading while the best results were obtained with a modifier percentage of 2.8%, although no differences were found between using 2.8 and 4.8%. It has been reported that the relation CO 2 /modifier, as well as the nature of the modifier, interfere in the affinity between the solute and the matrix [ 64 ]. For instance, García-Casas and others established that 10% v / v of acetone/DMSO (80%/20%)/CO 2 were the optimal conditions to impregnate mangiferin into silica [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, it is also highly selective and, by modulating some parameters such as pressure, temperature or time, it allows a precise control of both the sort and amount of compounds to be impregnated [ 13 , 17 , 19 ] while preserving their integrity [ 16 , 17 ]. In terms of supercritical solvents, carbon dioxide has shown to be rather efficient, because of its moderate critical point (31.1 °C and 73.8 bar), low price and high availability.…”
Section: Introductionmentioning
confidence: 99%
“…Although the supercritical impregnation of a polymer with a natural extract, such as olive leaf extract, has been previously reported [ 19 ], the usage of a bioactive impregnated polymer filament to feed a 3D printer is a whole new conception. Bioactive polymeric devices have been previously designed as films to be used as patches without any further transformation, while in our study, impregnated PLA filaments were fused using a 3D printer and modeled in order to produce biomedical functionalized devices.…”
Section: Introductionmentioning
confidence: 99%
“…The active substance closed in this way has a limited release from the finished product, which has found its practical application in the production of drugs with a controlled release time of active substances. In the process of impregnation, it is very important to select the right components of the matrix, which must be swollen by the supercritical fluid and active substances that must be soluble in it [ 113 , 114 , 115 , 116 , 117 , 118 , 119 ].…”
Section: Impregnation and Plasticizationmentioning
confidence: 99%